The Influence of Digital Literacy, Usability, and Convenience on Interest in Using Islamic Bank Mobile Banking for Customers in Gresik - Achmad Hadhirul Marwah (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
This study aims to analyze the influence of digital literacy, usability, and convenience on the interest in using mobile banking applications among Sharia Bank customers in Gresik. In today's digital era, the development of information technology encourages various sectors, including banking, to utilize mobile banking applications as a means to facilitate transactions and interactions with customers. Good digital literacy is expected to improve customer understanding in using application features. In addition, the usability and ease of use of mobile banking applications also play an important role in shaping customer interest in adopting them. This study uses a quantitative approach with a survey data collection method. Respondents in this study were Sharia Bank customers who use mobile banking applications in the Gresik area. The data obtained were analyzed using multiple linear regression tests. The results of this study are expected to provide insight for banks in increasing customer interest in using mobile banking applications by increasing digital literacy and improving the usability and convenience aspects of the application.